Gene Delivery: Inhaled Nanoformulated mRNA Polyplexes for Protein Production in Lung Epithelium (Adv. Mater. 8/2019). Issue 8 (19th February 2019) - Patel, Asha Kumari; Kaczmarek, James C.; Bose, Suman; Kauffman, Kevin J.; Mir, Faryal; Heartlein, Michael W.; DeRosa, Frank; Langer, Robert; Anderson, Daniel G.
Abstract : In vitro transcribed messenger RNA is nebulized using poly(beta amino esters) for inhalable delivery to the lung as described by Daniel G. Anderson and co‐workers in article number1805116 . Hyperbranched polymers are synthesized, which form stable mRNA‐polyplexes that distribute uniformly throughout the lungs of mice and are translated to reporter protein in the lung epithelium.